(untitled) (Ustozlar uchun, 2025)
article explores the significance of creative tasks in enhancing language learning for children. It discusses how creative activities can foster children’s imagination, critical thinking, and language acquisition skills. The paper highlights various creative tasks that teachers can incorporate into language lessons, such as storytelling, role-playing, and creating visual projects. Additionally, the article emphasizes the importance of a playful and interactive learning environment to boost children’s motivation and engagement in language learning. The study also suggests ways to adapt these tasks for different age groups and language proficiency levels, ensuring that they are both enjoyable and educational. Ultimately, creative tasks help children develop not only language skills but also emotional and social intelligence.